Acceptance of family doctors among residents in China: a cross-sectional study - Feng, Jing; Lei, Zihui; Li, Xinyan; Qu, Ge; Sun, Yuchao; Zheng, Yanling; Zuo, Yanli; Gan, Yong; Ye, Jun (Frontiers in Medicine, 2024)
Objectives: This study aimed to investigate the level of acceptance of family doctors (FDs) exhibited by residents in China.A cross-sectional study based on a structured self-administered questionnaire was conducted to investigate residents in eastern, central, and western China between September and December 2021. A multivariable stepwise logistic regression model was employed to identify the factors associated with health-seeking behavior after the signing of agreements concerning family doctor contract services (FDCS) as well as residents' willingness to change FDs.Results: Among the 2,394 respondents included in this research, 55.8% sought primary care from their FDs when they became ill, whereas 9.7% expressed a willingness to change FDs.Residents who reported high levels of satisfaction with FDCS [odds ratio (OR) = 2.162] and trust in FDs (OR = 1.430) were more likely to seek initial help from FDs. In addition, residents from central China (OR = 0.546) and western China (OR = 0.704) and those who exhibited a high level of trust in FDs (OR = 0.238) were less likely to change FDs.The level of FD acceptance among Chinese residents was relatively high.Satisfaction with FDCS and trust in FDs were associated with the acceptance of FDs among residents. FDs should make efforts to enhance the quality of health services as well as the overall health experience of residents.